2005
DOI: 10.1091/mbc.e05-01-0056
|View full text |Cite
|
Sign up to set email alerts
|

Dsl1p, Tip20p, and the Novel Dsl3(Sec39) Protein Are Required for the Stability of the Q/t-SNARE Complex at the Endoplasmic Reticulum in Yeast

Abstract: The "Dsl1p complex" in Saccharomyces cerevisiae, consisting of Dsl1p and Tip20p, is involved in Golgi-ER retrograde transport and it is functionally conserved from yeast to mammalian cells. To further characterize this complex, we analyzed the function of Dsl3p, a protein that interacts with Dsl1p in yeast two hybrids screens. DSL3, recently identified in a genome wide analysis of essential genes as SEC39, encodes a cytosolic protein of 82 kDa that is peripherally associated with membranes derived from the ER.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
154
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(165 citation statements)
references
References 80 publications
(133 reference statements)
9
154
0
2
Order By: Relevance
“…The Tip20 and Sec39 subunits of the Dsl1 complex, which regulates Golgi-to-ER transport and accelerates SNARE complex assembly in vitro, interact directly with the N-terminal regulatory domains of the tSNAREs Use1 and Sec20. These interactions are necessary for SNARE complex assembly (Diefenbacher et al, 2011;Kraynack et al, 2005;Ren et al, 2009;Tripathi et al, 2009). Similarly, all four subunits of mammalian GARP interact directly with Stx6, Stx16 and VAMP4, and regulate Stx6 SNARE complex assembly (Pérez-Victoria and Bonifacino, 2009;Pérez-Victoria et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The Tip20 and Sec39 subunits of the Dsl1 complex, which regulates Golgi-to-ER transport and accelerates SNARE complex assembly in vitro, interact directly with the N-terminal regulatory domains of the tSNAREs Use1 and Sec20. These interactions are necessary for SNARE complex assembly (Diefenbacher et al, 2011;Kraynack et al, 2005;Ren et al, 2009;Tripathi et al, 2009). Similarly, all four subunits of mammalian GARP interact directly with Stx6, Stx16 and VAMP4, and regulate Stx6 SNARE complex assembly (Pérez-Victoria and Bonifacino, 2009;Pérez-Victoria et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Dsl1 forms a complex with Dsl3/Sec39 and Tip20 to form the Dsl1 complex, another member of the CATCHR family of tethering complexes noted for their extended helical rod structures (Lees et al 2010). Further genetic and biochemical dissection of these proteins converged on a role in retrograde transport from the Golgi to the ER: tip20 and dsl1 mutants showed genetic interactions with a variety of ER-Golgi SNAREs (Sweet and Pelham 1993;Andag et al 2001;Kraynack et al 2005), tip20 mutants showed defects in fusion of COPI vesicles (Kamena and Spang 2004), the Dsl1 complex was localized to the ER (Kraynack et al 2005), and Dsl1 interacts directly with multiple components of the COPI coat (Andag and Schmitt 2003).…”
Section: Composition and Structure Of The Copi Coatmentioning
confidence: 99%
“…Sec39 itself binds to the N-terminal domain of the ER resident SNARE, Use1, via a region that likely lies proximal to the membrane , and Tip20 contains a second SNARE-binding site, interacting with the N-terminal domain of Sec20 ). In addition to binding individual SNAREs, the Dsl1 complex also promotes SNARE assembly and thus may serve two roles in fusion: maintaining individual SNAREs in an unpaired, receptive state, and scaffolding assembly of the fusogenic SNARE complex to promote fusion (Kraynack et al 2005;Ren et al 2009). An additional role in vesicle uncoating is suggested by the tendency of vesicles to accumulate en masse under conditions of Dsl1 depletion (Zink et al 2009): COPI shedding might be assisted by a Dsl1-COPI interaction that would prevent repolymerization of disassembled coat subunits, or could be driven by conformational changes in the Dsl1 complex that would capitalize on the ability of Dsl1 to interact with both the outer a-/e-COPI domain and a second site on the inner d-COP subunit to prize the coat from the membrane Zink et al 2009).…”
Section: Composition and Structure Of The Copi Coatmentioning
confidence: 99%
“…Moreover, the interaction of Dsl1 and COPI suggested that Dsl1 could be recruited to retrograde vesicles. We therefore took advantage of a COPII budding assay (22) to monitor the incorporation of selected subunits of the Dsl1 complex and SNAREs (Fig. 4A).…”
Section: Isolation Of Dsl1mentioning
confidence: 99%